The 2006 pfeiffer annual : (Pfeiffer, 2006)
The Pfeiffer Annual: Human Resource Management delivers the most up-to-date thinking on issues that are core to the modern HR manager's role; the series covers a broad range of topics such as leadership and succession planning, compensation and benefits, recruitment and selection, compliance and legal, employee and labor relations, wellness and safety, HR information systems, HR planning, and international HRM, among others. The Annual will become the anchor in your professional library, providing key knowledge, ideas, best practices, and benchmarking data